Efektifitas Penerapan Individual Work System untuk Meningkatkan Kemandirian Penyelesaian Tugas Anak dengan Autisme - adinda istiqomah; Dewi Retno Suminar (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
The deficit in independen can be seen on the teacher often helps or directs children with ASD (Autism Spectrum Disorder) to complete tasks. The aim of this study is to investigate  the effectiveness of Individual Work System for students with autism. The research is being conducted by applying individual work system for children with autism to improve completing the task. This research uses quasi experimental using reversal design A-B design in five subjects diagnosed with mild autism, aged elementary school, had problems in completing the tasks and have ability to simple intruction. The data collection tool uses observations that assess off-task/on-task behavior, teacher prompting, task completion. Data obtained were analyzed using Wilcoxon statistical test. The result showed that the intervention using that idividual work system was effective increase independence of task completion for children with ASD (p=0.04). Observations on all subjects showed increased on-task behavior, increased task completion, and reduced teacher prompting.